The epidemiology of stress fractures in collegiate student-athletes, 2004-2005 through 2013-2014 academic years - Rizzone, K. H.; Ackerman, K. E.; Roos, K. G.; Dompier, T. P.; Kerr, Z. Y. (Journal of Human Sport & Exercise, 2017)
Context: Stress fractures are injuries caused by cumulative, repetitive stress that leads to abnormal bone remodeling. Specific populations, including female athletes and endurance athletes, are at higher risk than the general athletic population. Whereas more than 460?000 individuals participate in collegiate athletics in the United States, no large study has been conducted to determine the incidence of stress fractures in collegiate athletes.